2017
DOI: 10.1002/erv.2540
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot, Multicentre Pragmatic Randomised Trial to Explore the Impact of Carer Skills Training on Carer and Patient Behaviours: Testing the Cognitive Interpersonal Model in Adolescent Anorexia Nervosa

Abstract: The provision of self-management materials for carers to standard treatment for adolescent anorexia nervosa shows benefits for both carers and patients. This could be integrated as a form of early intervention in primary care. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 43 publications
4
54
1
3
Order By: Relevance
“…In regard to the effect of the interventions on patients, it is worth noting that ED symptoms and behaviours, psychological distress, and psychosocial impairment related to the domestic area significantly reduced after both interventions. Results were similar to those reported by Hodsoll et al () and Whitney et al (), where patients' improvement was maintained in a follow‐up period of 1 to 3 years. However, this is contrary to our study where improvement was only shown immediately following the intervention and was not maintained at the 3‐month follow‐up assessment.…”
Section: Discussionsupporting
confidence: 90%
“…In regard to the effect of the interventions on patients, it is worth noting that ED symptoms and behaviours, psychological distress, and psychosocial impairment related to the domestic area significantly reduced after both interventions. Results were similar to those reported by Hodsoll et al () and Whitney et al (), where patients' improvement was maintained in a follow‐up period of 1 to 3 years. However, this is contrary to our study where improvement was only shown immediately following the intervention and was not maintained at the 3‐month follow‐up assessment.…”
Section: Discussionsupporting
confidence: 90%
“…In this latest iteration of the cognitive interpersonal model, we have described treatments targeting modifiable elements. Increasing social connection through encouraging a collaborative inclusive approach towards recovery, by increasing the knowledge and skills of family members, decreases the need for high-intensity care (day or inpatient) and reduces carer burden and patient isolation [49][50][51]136]. Treatment using MANTRA focuses on both inter and intrapersonal model elements [55,56].…”
Section: Resultsmentioning
confidence: 99%
“…An improved understanding about the illness reduces carer distress and burden [35,45,47,48]. Several studies have found that augmenting treatment with these resources for carers reduces both carer and service burden [49][50][51]. Often this has involved a 'train the trainer' approach whereby carers and patients deliver these interventions.…”
Section: Targeting Stressful Interpersonal Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This targets some of interpersonal maintaining factors that arise as a consequence of the illness and aims to increase social connection (Treasure & Nazar, 2016). Augmenting both inpatient and adolescent outpatient treatment with ECHO for carers, not only reduces carer burden and distress but also reduces re-admission rates and symptoms in patients (Hibbs, Magill, et al, 2015;Hodsoll et al, 2017;Magill et al, 2016).…”
mentioning
confidence: 99%